Konsep Uang Islam: Antara Uang Komoditas atau Uang Fiat - Khoirul Umam (University of Darussalam Gontor, 2016)
Recent monetary crises have brought back the interest of scholars especially Muslim scholars to re-evaluate the current fiat monetary system. A group of Muslim economists believe that the source of problems is a form of fiat money. However, a larger group of Muslim economists prefer to set fiat money according to the rules of Sharia. This paper attempts to discuss the opinion of these two groups, so then offers the concept of money in Islam. The first group argue that the fiat money creates a seigniorage which is the cause of inflation, inequity of wealth distribution and monetary and financial crisis. Fiat money is also the soul of banking fractional reserve system which leads to the problem of inflation, business cycles and injustice distribution of wealth. Lastly, fiat money sytem with interest result in an inflationary economy. Besides these three, there is a belief that the money according to Islam must be commodity money. The second group counter that the strict rules for monetary management is proved to minimize the use of seigniorage so that inflation can be controlled. In fact, the fiat money and fractional reserve system support economic expansion so that the community can enjoy the economic growth. Furthermore, the business cycle is not just happening on a fiat money system but also a part of the commodity money system. Indeed, money in Islam must be a commodity is not agreed by the majority of fiqh scholars. However, in the context of international currency, the issue of injustice and the causes of the crisis becomes challenging issue. The first group propose to change international currency to commodity money, while the second group offers a monetary union as in the case of Europe. Finally, the concept of money is not about the form of money, but rather whether the money can be a just medium of exchange and measure of value for the goods and services.